2014
DOI: 10.1155/2014/260939
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term and Short-Term Effects of Hemodialysis on Liver Function Evaluated Using the Galactose Single-Point Test

Abstract: Aim. The galactose single-point (GSP) test assesses functioning liver mass by measuring the galactose concentration in the blood 1 hour after its administration. The purpose of this study was to investigate the impact of hemodialysis (HD) on short-term and long-term liver function by use of GSP test. Methods. Seventy-four patients on maintenance HD (46 males and 28 females, 60.38 ± 11.86 years) with a mean time on HD of 60.77 ± 48.31 months were studied. The GSP values were compared in two groups: (1) before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…] In our study serum total protein was 6.6 g/dl. However, studies have suggested that plasma protein should be used as a single criterion for nutritional status, due to other contributing factors including age, comorbidities, hypervolemia, and weight loss [12] .The mean SGOT and SGPT were in normal value ranges a result supported by Hou et alwho reported that there was no observed impairment in the liver function of haemodialysis patients [13] .The mean potassium level of all patients in this study was less than 4 me/L (3.72meq/L; SD 0.84), a study by Kirtankar et al reported that serum potassium levels of 3.5-4 meq/L could be associated with higher risk of mortality. The mean sodium level of all patients in this study was 134 meq/l (SD 4.9); low sodium levels were associated with higher risk of mortality according to a study by Sun et al [14] In the western world most patients receive thrice weekly haemodialysis whereas in India many patients receive twice weekly haemodialysis.…”
Section: Discussionmentioning
confidence: 88%
“…] In our study serum total protein was 6.6 g/dl. However, studies have suggested that plasma protein should be used as a single criterion for nutritional status, due to other contributing factors including age, comorbidities, hypervolemia, and weight loss [12] .The mean SGOT and SGPT were in normal value ranges a result supported by Hou et alwho reported that there was no observed impairment in the liver function of haemodialysis patients [13] .The mean potassium level of all patients in this study was less than 4 me/L (3.72meq/L; SD 0.84), a study by Kirtankar et al reported that serum potassium levels of 3.5-4 meq/L could be associated with higher risk of mortality. The mean sodium level of all patients in this study was 134 meq/l (SD 4.9); low sodium levels were associated with higher risk of mortality according to a study by Sun et al [14] In the western world most patients receive thrice weekly haemodialysis whereas in India many patients receive twice weekly haemodialysis.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have been proposed for choosing different cutpoints of short-term and long-term duration of hemodialysis. For example, Hou et al (2014) defined a long-term of hemodialysis as at least one year of hemodialysis. Another study defined as an average 51 months for the long period of hemodialysis treatment ( Chazot et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that renal perfusion significantly declines at peak dialytic stress, 10 representing repetitive, intradialytic episodes of ischemic acute kidney injury. 52 The potential negative relationship between kidney injury and the liver's clearance function has been previously discussed in the context of acute kidney injury 53,54 and ESRD, 13,55 and may be an important additional factor contributing to HD-induced hepatic dysfunction and increased endotoxemia.…”
Section: Clinical Researchmentioning
confidence: 99%